Recent Advances in the Treatment of Rheumatoid Arthritis - Mahajan, Tina D. (Curr Opin Rheumatol, 2018)
PURPOSE OF REVIEW: Therapies for rheumatoid arthritis (RA) continue to expand rapidly. The purpose of this review is to discuss novel treatment options, including biosimilars, that are available, as well as to highlight promising agents in development. The purpose is also to discuss new emerging safety signals associated with these drugs and to discuss strategies in tapering therapy. RECENT FINDINGS: There are several novel RA therapies. These include the interleukin 6 receptor blocker sarilumab, which was approved in 2017. In aggregate, the sarilumab studies show that it is effective in RA, including patients with incomplete responses to methotrexate and anti-tumor necrosis factor inhibitor, showing superior efficacy when used in higher dose (200 mg every two weeks) to standard-dose adalilumab. The two biosimilar drugs currently approved are CT-P13 and SB2, which are based on the reference product infliximab. Other drugs that are currently being studied include the interleukin-6 cytokine blocker sarikumab, the small targeted molecule filgotinib, and many new biosimilars. Baracitinib failed to achieve approval by the FDA primarily over perceived safety concerns. Although this review summarizes trials examining biologic tapering, additional data is needed to guide clinicians in regards to treatment de-escalation in RA. SUMMARY: With the greatly expanded armamentarium of RA treatment options available, it is important for clinicians to understand the data regarding drug efficacy and safety. With remission increasingly attainable, effective drug tapering strategies are needed. While tapering trials do exist, more studies will be needed to help guide clinical practice.